BRIDGING WORKPLACE DEMOCRACY AND SUPPLY CHAIN INTEGRATION THROUGH HIGH INVOLVEMENT OF HUMAN RESOURCE PRACTICES - Siriyanun, Sirinya; Mukem, Abdunrohman; Jermsittiparsert, Kittisak (International Journal of Supply Chain Management, 2019)
Human resource management has taken a sharp turn in 21st century towards high involvement practices. Recruiters are shifting towards such high involvement practices to integrate the business functions with more efficiency especially supply chain. However, such integration seems less effective without a strong democratic culture in organization. This study has determined the impact of workplace democracy on supply chain integration in Thailandâ??s manufacturing sector where democratic practices have been started nourishing in factory areas. Moreover, mediating roles of high involvement HRM practices such as employee incentives, skills and participation have also been analyzed in relationship between workplace democracy and supply chain integration. Data has been collected from Thailandâ??s manufacturing sector and middle management was surveyed through structured questionnaire whose data was then analyzed by applying confirmatory factor analysis and structural equation modeling. Results have highlighted that workplace democracy can significantly enhance supply chain integration while almost all high involvement HR practices were found as significant mediators in relationship between democracy and integration. Originality of this study is there in outcome variable which was supply chain integrity that was never tested before as consequence of democracy or high involvement practices. This study has its implications, limitations and future research directions too.